Integration of Christian Values with Local Wisdom in Digital Learning Media: Literature Review - Rangga, Oktavianus; Gulo, Rezeki Putra (Fakultas Keguruan dan Ilmu Pendidikan Kristen IAKN Palangka Raya, 2025)
This research aims to examine the integration of Christian values with local wisdom through digital learning media within the context of Christian Religious Education (CRE). The problem addressed is the lack of learning media that contextually and relevantly accommodates Christian values and local culture in line with the development of digital technology. This research employs a descriptive qualitative method with a library research approach through a systematic review of relevant academic literature. The novelty of this research lies in the design of a conceptual model for digital media that combines Christian faith values such as love, justice, and service with local cultural elements like folklore, regional songs, and traditional symbols. The research findings indicate that this integration can enhance the relevance, participation, and understanding of Christian teachings among students, while simultaneously strengthening their cultural identity. These findings offer a theoretical contribution to the development of inculturation-based CRE literature and a practical contribution for Christian educators in the digital age.